Efficient extracellular expression and antimicrobial activity of Procambarus clarkii invertebrate-type lysozyme in Pichia pastoris - SHUI Yan; GUAN Zhengbing; YE Junxian; SHI Yonghong; LIU Guofeng; XU Zenghong (浙江大学学报. 农业与生命科学版)
A Pichia pastoris expression method for the efficient extracellular production of Procambarus clarkii invertebrate-type lysozyme 1 (pc-iLys1) was established. First, the synthetic codon-optimized cDNA encoding pc-iLys1 was expressed in the P. pastoris SMD1168 with a molecular mass of about 17.1 kDa. The expression condition in a shaking flask was optimized and the best condition for pc-iLys1 production was as follow: the cells were cultured in pH 7.0 and grown at 28℃ for 96 h supplemented with 1.5% methanol. High cell density fermentation was then performed using a fed-batch strategy in a 5 L fermenter. Extracellular lytic activity and dry cell mass concentration reached to 2 052.6 U/mL and 98.1 g/L after 120 h, respectively. The purified recombinant pc-iLys1 exhibited extensive antimicrobial activities toward the selected bacteria (including Gram-positive and Gram-negative bacteria). In a word, the P. pastoris expression strain and the method established in this work are promising for the industrial high-yield production of pc-iLys1 protein, and the recombinant pc-iLys1 has potential as an antimicrobial agent for treating the infectious diseases of P. clarkii.